The Spirituality of Jesus for the Unchurched and the Unaffiliated: A Pentecostal-Charismatic Perspective - Scott Lewis Adams (Religions, 2022)
This article calls for an examination of the spirituality of Jesus in light of the unique historical and theological distinctives of the Pentecostal-Charismatic movement. Although the topic of spirituality is wide and deep, this study will approach it as personally transformative Christian experiences and practices that enrich one’s life and the lives of others. By drawing from the research of statisticians and social scientists, I will discuss notable ways in which the Pentecostal-Charismatic movement has the potential to make the spirituality of Jesus accessible to the unchurched and the unaffiliated (nones) in the United States. The results of my research reveal that, although such persons do not regularly attend church, they are, in part, open to religious experiences and desire a deeper spirituality. A such, this paper shows that the experience-based, supernaturally empowered, every-member-is-a-minister nature of the Pentecostal-Charismatic movement may indeed appeal to and meet the needs of certain unchurched and the unaffiliated persons. Furthermore, this paper will conclude by presenting suggestions for reform that may enhance this movement’s ability to reach the unchurched and unaffiliated in days to come. In the final analysis, this paper provides a historical foundation and theoretical framework from which Pentecostal-Charismatic influences upon such groups can be further assessed.